Caracterización morfo-agronómica de 20 accesiones de fréjol arbustivo (Phaseolus vulgaris L.) en dos épocas de siembra en el recinto Galápagos, cantón Echeandía, provincia de Bolívar - Allán Granja, Cristopher Danilo (2017)
The cultivation of arbustive and voluble bean is one of the most important in the world after maize, wheat, rice and potatoes. The importance is because is rich in proteins, fibers and minerals and biological nitrogen fixation (FBN) to the soil, being key in the rotation of crops to contribute to good agricultural practices (GAP) and thus to food security and sovereignty. This research was carried out in the Galápagos precinct of canton Echeandía at an altitude of 415 m and two sowing times on June 2 and 16, 2016. The objectives were: i) To evaluate the morphoagronomic characteristics of 20 accessions of bush beans in soft and dry grains. Ii) Validate the morphoagronomic behavior of 20 accessions of bush bean, in two planting seasons. Iii) Select the best accessions and cultivars of bush bean in tender and dry for this agroecological zone. A block design was applied with 20 treatments (beans accessions ) twice repeticiones and planting times. The main performance components and morphological descriptions were evaluated. We performed Variance Analysis (ADEVA), Tukey Test, Correlation and Linear Regression.The main results were: the highest average yield in tender and dry was evaluated in the first sowing season with 2245 kg / ha in tender and 1151 kg / ha in dry. The highest average yield in tender and dry at the two planting times was recorded in treatment T14 (Black Bean of Chillanes) with 3172 kg / ha and 1409 kg / ha respectively. The components that increased dry yield were: vegetative vigor, load and performance in tender. It is clear that climate change and the indicators that influenced the results to more than genetic ones were: altitude, temperature (heat), drought stress and high rates of evapotranspiration. This study allowed the selection of T14 treatments as the best accessions for this agroecological zone; T20; T18; T5; T7; T13 on its order. Finally, this research helped to select promising germplasms of arbustive bean that demand the different segments of the market such as precocious cycle, grain of the large, medium and small size of dry colors like canaries (yellow), solid reds, mottled red, black, white and Brown.